The Song of the Adarna [videorecording] a documentary on selected Philippine traditional folk media. ([Quezon City] Philippine Information Agency)
Features the folk media of the Philippines like the epic, pasyon, comedia and zarzuela preserved by the oral tradition of Philippine ethnic groups.
Keywords: Folk literature -- Philippines; Philippine literature